2018
DOI: 10.1103/physreva.98.023612
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical quantum phase transitions in systems with broken continuous time and space translation symmetries

Abstract: Spontaneous breaking of continuous time translation symmetry into a discrete one is related to time crystal formation. While the phenomenon is not possible in the ground state of a timeindependent many-body system, it can occur in an excited eigenstate. Here, we concentrate on bosons on a ring with attractive contact interactions and analyze a quantum quench from the time crystal regime to the non-interacting regime. We show that dynamical quantum phase transitions can be observed where the return probability … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, because the dynamics of systems under time-periodic modulations has led to fascinating discoveries like Floquet topological states [20][21][22][23][24] and discrete time crystals [25][26][27], it is urgent to investigate how DQPTs may occur in such Floquet systems. Along this avenue, there have been scattered studies, but still with the notion that DQPTs are best aroused by a quench to some system parameters [28,29]. Here we introduce a novel class of DQPTs, termed Floquet DQPTs, which can be regarded as intrinsic features of systems with time-periodic modulations.…”
mentioning
confidence: 99%
“…3, where the doubly critical phase disappears at large α. On the other hand, the purely long-range hopping case β → ∞ always contains a doubly critical phase for α 3.6223, as follows from (38) and (39), but it does not display the triply critical phase for any α value.…”
Section: The α > 3 Regimementioning
confidence: 97%
“…Additionally, this dynamical critical point was shown to coincide with that of the type of dynamical phase transition based on a local order parameter [18,[20][21][22][23][24][25]. Also recently, the theory of DQPT has been extended to Floquet systems [38][39][40] and models with many-body localized phases [41,42]. DQPTs in nonintegrable models have been studied in, for instance, Ref.…”
Section: Introductionmentioning
confidence: 99%